Eksplorasi Etnomatematika pada Aktivitas Menenun Masyarakat Ile Ape Kabupaten Lembata dan Integrasinya dalam Pembelajaran Matematika - Claudia Inda Permata Masan; Wara Sabon Dominikus; Aleksius Madu (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Ethnomathematics is a science that describes the practice of mathematics in the culture that grows and develops in society, one of which is weaving. This study aims to describe the ethnomathematics found in the weaving activities of the Ile Ape community, describe the mathematical concepts that contain ethnomathematics in the weaving activities of the Ile Ape community, and describe how to integrate ethnomathematics from the weaving activities of the Ile Ape community into mathematics learning. The method used in this study is a qualitative research method with data collection techniques using triangulation and inductive data analysis. Based on the analysis, it was found that the weaving activities of the Ile Ape community include counting, measuring, comparing, explaining, and designing. Meanwhile, the mathematical concepts associated with ethnomathematics in the weaving activities of the Ile Ape community include addition and multiplication operations, units of time, mathematical logic, measurement, geometry, and geometric transformations. Ethnomathematics in weaving activities can be used as a learning resource by identifying mathematical concepts and then linking these mathematical concepts to school materials.